Pengaruh Komunikasi dan Motivasi Terhadap Semangat Kerja Karyawan pada CV. Karya Penta - Widia Astuti; Natal Indra (Jurnal bintang manajemen, 2025)
This research aims to find out how much influence communication and motivation have on employee morale at CV. Penta's work on the head office. The research method used is a quantitative method approach with data collection techniques using probability sampling with a population of 108 employees and samples taken using the Slovin formula, namely 52 respondents. Data were collected using a questionnaire in ordinal (Likert) scale units. Data processing uses SPSS 26 software for instrument testing, multiple linear regression analysis, and hypothesis testing. The research results show that both partially and simultaneously communication and motivation have a positive effect on the performance of CV employees morale. Penta's work. This is because 446,808 f count > f table, where f table is 3,18 and is supported by a significance value of 0.000 where the condition for accepting the hypothesis is a significance value of less than 0.05.